PENINGKATAN KINERJA KOPERASI MELALUI PENDAMPINGAN MANAJEMEN KEUANGAN PADA KOPERASI 64 BAHARI SURABAYA - Wasiaturrahma, Wasiaturrahma; Sulistyowati, Chorry; Heriyati, Dina; Ajija, Shochrul Rohmatul (Universitas PGRI Yogyakarta, 2020)
64 Bahari Cooperative, located in Kedung Cowek Sub-District, Kenjeran District, has a growing cooperative asset but the management is still having difficulty in preparing financial reports manually. The main agenda in this service program is to procure online-based Sharia cooperative accounting software for fishermen cooperatives. This can be done because the cooperative already has a laptop, most members already have an android mobile phone, and internet access is quite adequate because it is located in the Surabaya City area. In addition, online systems are considered cheaper than offline software because cooperatives do not need to incur server procurement costs that require large costs. Another advantage is that it can be accessed by members wherever and whenever. The result of this program is an increase in the ability of 64 Bahari Cooperative managers to make financial reports independently.